Exodus ; v. 2 - Meyer, Frederick Brotherton, 1847-1929 (London, UK Marshall, Morgan and Scott, 1952)
Contents : v. 2 : Exodus chapters 20-40
Donated by Mrs McElwaine.
Keywords: Bible. O.T. Exodus XX-XL -- commentaries